The Effect Of Cassava Leaf (Manihot Esculenta) Therapy On HB Levels In Pregnant Women With TMS 2 At The Balibunga Community Health Center - Nurlaeli F; Retno Dewi Prisusanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Anemia in pregnancy remains a common public health problem and may lead to adverse outcomes for both the mother and the fetus, highlighting the need for effective and practical interventions. This study aimed to analyze the effect of cassava leaf (Manihot esculenta) consumption on hemoglobin levels among second-trimester pregnant women at UPT Puskesmas Rum Balibunga. A quasi-experimental study with a pretest–posttest design without a control group was conducted. The sample consisted of 30 second-trimester pregnant women with mild anemia, selected using purposive sampling. The intervention involved daily consumption of cassava leaves for 14 consecutive days. Hemoglobin levels were measured before and after the intervention using standardized examination tools. The results demonstrated a significant increase in hemoglobin levels following cassava leaf consumption, with a mean increase of 1.2 g/dL. These findings suggest that cassava leaves, which are rich in iron, vitamin C, and protein, can enhance hemoglobin synthesis and serve as a local food-based nutritional intervention. Therefore, cassava leaf consumption can be recommended as an alternative or complementary strategy for preventing and managing anemia among second-trimester pregnant women in primary healthcare settings.